The Public Library and Social Media: A Case Study from Tromsø, Norway - Skare, Roswitha (Proceedings from the Document Academy, 2018)
Historically, archives, libraries and museums (ALM) have been perceived as institutions providing infrastructure for an open and enlightened public discourse. The Norwegian Public Libraries Act focuses on public libraries being providers of knowledge and cultural expressions, agents of popular enlightenment, local meeting places and arenas of debate and participation in the public sphere. But public libraries are also supposed to keep up with the technological development and to offer digital services to the inhabitants of their municipality. This paper presents the first findings of an ongoing research project investigating the relationship between physical meetings at the Tromsø public library and posts at the library’s Facebook-page.